Makzin: Identifying Design Practices In Tablet Magazines - Trinnaman, Brad (My University, 2014)
The practice of editorial design has been continually refining itself as an effective communication method of visual story telling for the last 200 years. In print, magazines are designed in a way that gives readers a hybrid experience between the daily information delivery of newspapers and the enduring content of books. There are many different solutions to deliver news and information digitally. Tablet computers, have introduced new possibilities for designers to create magazine applications that have the rich reading experience found in print, but enhanced with interactivity. Makzin is a publication application created to catalogue outstanding tablet magazines in the digital publishing landscape, identify best practices used in their creation, and disclose usability behaviors.
Thesis (Master's)--University of Washington, 2014
Keywords: Design; Editorial; iPad Application; Tablet Computer; User Studies; Design; fine arts